Psychological Impact of the COVID-19 Pandemic on Healthcare Professionals in Tunisia: Risk and Protective Factors - Hammami, Ahmed Sami; Jellazi, Mohamed; Mahjoub, Lobna; Fedhila, Maya; Ouali, Sonia (Frontiers in Psychology, 2021)
Background: Our study aimed to evaluate the magnitude of different psychological outcomes among Tunisian healthcare professionals (HCPs) during the first wave of the coronavirus disease 2019 (COVID-19) pandemic, and to identify the associated factors. Methods: Healthcare professionals completed a cross-sectional questionnaire during a 3-week period in the first wave of the COVID-19 pandemic in Tunisia. The survey collected demographic information, factors that may interfere with the psychological outcomes, behavioral changes, and mental health measures. Mental health was assessed using three scales: the Seven-Item Insomnia Severity Index, the Two-Item Patient Health Questionnaire, and the Two-Item Generalized Anxiety Disorder instrument. Multivariable logistic regression was conducted to identify factors associated with psychological outcomes. Results: A total of 503 HCPs successfully completed the survey, and 493 agreed to enroll in the study: 411 (83.4%) physicians, 323 (64.2%) women, and 271 (55%) with a second-line work position. A significant proportion of HCPs had anxiety (35.7%), depression (35.1%), and insomnia (23.7%). Women, those with a psychiatric history, and those using public transportation had higher proportions for overall symptoms compared with other groups, for example, depression in 44.9% of female participants vs. 18.2% of male participants (p = 0.00). Those with a previous medical history and nurses had more anxiety and insomnia compared with other groups, for example, anxiety in 45.1% of nurses, 36.1% of interns/residents, and 27.5% of attending physicians (p = 0.04). Multivariable logistic regression showed that female gender was a risk factor for all psychological outcomes, whereas psychiatric history was a risk factor for both anxiety and insomnia [odds ratio (OR) = 2.86, 95% CI 1.78–4.60, p = 0.00 for insomnia]. Using protective equipment was associated with a lower risk for depression (OR = 0.41, 95% CI 0.27–0.62, p = 0.00) and anxiety. Physical activity was also protective against depression and anxiety (OR = 0.41, 95% CI 0.25–0.67, p = 0.00). Conclusion: Psychological symptoms are usually overlooked or dismissed by HCPs, although the COVID-19 pandemic played a major role in exacerbating this burden. Prompt psychological support should be endorsed and simple measures, such as physical activity and ensuring the availability of personal protective equipment, are paramount to improve mental health outcomes and the quality of care provided to patients.